The Representation of Critical Thinking Skills in Reading Materials of Junior High School English Textbooks: A Systematic Literature Review - Wulan Widya Istiyana; Nadila Aulia Ashyurin; Indah Juniasari T; Yati Kurniati; Osy Benu Ismail; Elyza Martiarini (CV. Kalimasada Group Profesional, 2026)
Critical thinking is an essential competency in twenty-first-century learning that should be integrated into English textbooks, particularly in reading materials. This study aimed to identify research trends, analyze research methods and theoretical frameworks, map critical thinking indicators, and formulate recommendations for English textbook development. This study employed a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. A total of ten studies meeting the inclusion criteria were systematically reviewed and synthesized. The findings revealed an increasing trend in research on critical thinking representation in English textbooks during 2022–2025. Most studies employed content analysis and adopted the Revised Bloom's Taxonomy as the primary analytical framework. The review further demonstrated that reading materials were predominantly characterized by Lower Order Thinking Skills (LOTS) activities. Indicators related to information analysis, reasoning, and information comparison were most frequently represented, whereas evaluation, reflection, problem-solving, and decision-making appeared less frequently. These findings suggest that English reading materials have not yet comprehensively fostered critical thinking skills. Therefore, English textbook developers and teachers should systematically incorporate Higher Order Thinking Skills (HOTS) activities into reading instruction to promote students' critical engagement, reflective thinking, and problem-solving abilities.